Thinking about the Baby : Gender and Transitions into Parenthood. - Walzer, Susan (Temple University Press, 2010)
Many new mothers and fathers are surprised at how they change as individuals and as couples after a baby is born. Susan Walzer's interviews explore the tendency for men and women to experience their transitions into parenthood in different ways--a pattern that has been linked to marital stress. How do new mothers and fathers think about babies, and what is the influence of parental consciousness in reproducing motherhood and fatherhood as different experiences? The reports of new parents in this book illustrate the power of gendered cultural imagery in how women and men think about their rol.